DIFFERENT PERCENTAGE OF WATER EXCHANGE ON GROWTH OF CORAL TROUT GROUPER FINGERLING (Plectropomus leopardus) - Titiek Aslianti (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2010)
Coral trout grouper (Plectropomus leopardus) is the prospective aquaculture commodities with a high demand. Fingerling culture is the one of shortly rearing time methods for grow out in net-cages in order to produce continuously. Two hundred fishes with initial total length 16.6±0.5 cm and 72.2±7.6 g of body weight were stocked in each of three of concrete tanks of 4m3 seawater. Water replace as a treatment was applied i.e. A (200%/day), B (300%/day) and C (400%/day).respectively. Feeding frequency of pellet was done twice a day of about 3 - 5% of body weight. Survival and growth of fishes were monitored during two-month period. The result showed that the different percentage of water replace had a significant role in increasing the growth and survival rate of the fishes. Water replaced of 400% daily (treatment C) gave the best survival rate (97%) and growth performance (TL 21.61±0,54 cm; BW 156.84±1.05 g). In contrast, the treatment B (300%/day) and A (200%/day) resulted in a lower survival and growth , i.e. (SR 95.5%; TL 19.51±0.52 cm; BW 140.96±0.08 g) and A (SR 93%; TL 19.08±0.30 cm; BW 132.2±2.65 g)., respectively.Keywords: Coral trout grouper, growth, survival rate, water exchange